MENINGKATKAN MOTIVASI BELAJAR SISWA MELALUI KOMBINASI GOOGLE CLASSROOM DAN GOOGLE MEET SEBAGAI MEDIA PEMBELAJARAN AKIBAT PANDEMI COVID-19 PADA MATA PELAJARAN KEWIRAUSAHAAN SISWA KELAS XI RPL DI SMK KOPERASI PONTIANAK - Jumrah Jumrah; Husni Syahrudin; Syamsuri Syamsuri (Universitas Tanjungpura, 2021)
AbstractThis study aims to describe and analyze the application of a combination of GoogleClassroom and Google Meet learning media in increasing student motivation inentrepreneurship subjects for class XI RPL at SMK Koperasi Pontianak. This research usesclassroom action research (CAR). The subjects in this study were students of class XI RPL atSMK Koperasi Pontianak in the odd semester of the 2019-2020 school year, totaling 34students. The data involved in this study are qualitative and quantitative data. The researchinstruments used by the researcher are: Learning Implementation Observation Sheet, StudentLearning Motivation Questionnaire, Written Test and Documentation. The data analysistechnique used is data presentation. Triangulation, and drawing conclusions. This classroomaction research is planned in several cycles, with planning procedures. Implementation ofaction, observation and reflection. The student learning outcomes starting from before theaction was carried out until the third cycle also increased. The percentage of student learningoutcomes in the pre-cycle (63.53%) increased in the first cycle (65.57%), increased again inthe second cycle (71.5%) and increased again in the third cycle (77.64%). Based on thedescription above, it can be concluded that the application of a combination of GoogleClassroom and Google Meet learning media can increase student learning motivation inentrepreneurship subjects in class XI RPL at SMK Koperasi Pontianak.Keywords: Motivation to Learn, Google Classroom, Google Meet, Learning Media, Covid-19